2022
DOI: 10.1177/03635465221078033
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Description of the Lateral Patellofemoral Complex: Anatomy and Anisometry

Abstract: Background: The lateral patellofemoral complex (LPFC) is an important stabilizer of the patella composed of the lateral retinacular structures including the lateral patellofemoral ligament (LPFL), the lateral patellomeniscal ligament (LPML), and the lateral patellotibial ligament (LPTL). While the isolated anatomy of the LPFL has been previously described, no previous study has investigated the entirety of the LPFC structure, length changes, and radiographic landmarks. An understanding of LPFC anatomy is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Specifically, a previous study from our institution demonstrated that the LPFL is significantly looser at 45° to 90° of flexion compared with full extension. 14 Interestingly, both reconstruction groups appeared to mimic this loosening of the native LPFL up to 60°. In contrast to that study, however, the LRR and reconstruction groups in the current investigation had a significant decrease in medial patellar translation from 60° to 90°, returning to a value similar to that observed in full extension.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Specifically, a previous study from our institution demonstrated that the LPFL is significantly looser at 45° to 90° of flexion compared with full extension. 14 Interestingly, both reconstruction groups appeared to mimic this loosening of the native LPFL up to 60°. In contrast to that study, however, the LRR and reconstruction groups in the current investigation had a significant decrease in medial patellar translation from 60° to 90°, returning to a value similar to that observed in full extension.…”
Section: Discussionmentioning
confidence: 93%
“…2,5 In this study, 2 anchor locations along the lateral aspect of the patella were utilized (superolateral and proximal to the distal aspect of the lateral facet of the articular surface) that corresponded with previous anatomic descriptions of the patellar insertion of the LPFC. 14 In addition, in this study, fixation of the graft was performed with the knee in full extension without additional direct tension applied. This approach mirrors the senior author's approach to MPFL reconstruction to prevent overtensioning of the graft.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations